2007
DOI: 10.1007/s00125-007-0654-8
|View full text |Cite
|
Sign up to set email alerts
|

C3H/HeJ mice carrying a toll-like receptor 4 mutation are protected against the development of insulin resistance in white adipose tissue in response to a high-fat diet

Abstract: Aims/hypothesis Inflammation is associated with obesity and has been implicated in the development of diabetes and atherosclerosis. During gram-negative bacterial infection, lipopolysaccharide causes an inflammatory reaction via toll-like receptor 4 (TLR4), which has an essential function in the induction of innate and adaptative immunity. Our aim was to determine what role TLR4 plays in the development of metabolic phenotypes during high-fat feeding. Materials and methods We evaluated metabolic consequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
247
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(286 citation statements)
references
References 57 publications
12
247
0
4
Order By: Relevance
“…Our data demonstrate that in absence of CD14, a high-fat diet could not induce inflammation as reflected by the total blunting of cytokine expression augmentation in the liver and adipose depot. Similarly, we recently reported that TLR4 mutant mice are protected against adipose tissue insulin resistance (44). Our finding is complementary to recent data that showed that free fatty acids can bind TLR4 to activate cells from the innate immune system (6) leading to the secretion of cytokines.…”
Section: Discussionsupporting
confidence: 88%
“…Our data demonstrate that in absence of CD14, a high-fat diet could not induce inflammation as reflected by the total blunting of cytokine expression augmentation in the liver and adipose depot. Similarly, we recently reported that TLR4 mutant mice are protected against adipose tissue insulin resistance (44). Our finding is complementary to recent data that showed that free fatty acids can bind TLR4 to activate cells from the innate immune system (6) leading to the secretion of cytokines.…”
Section: Discussionsupporting
confidence: 88%
“…Lack of Tlr4 in mice fed a HFD resulted in protection against obesity 67 , insulin resistance, 68 and inflammation in adipose tissues 69,70 , liver, skeletal muscle 71 , and vasculature 72 . Specific deletion of Tlr4 in haematopoietic cells ameliorated insulin resistance in hepatic and adipose tissue 73 and mice with a specific loss of Tlr4 in hepatocytes exhibited improved glucose tolerance, enhanced insulin sensitivity, and ameliorated hepatic steatosis 74 .…”
Section: [H3] Tlr4mentioning
confidence: 99%
“…Indeed, deficiency of Toll-like receptor 4 (TLR4) or TLR4 signaling protects against obesity-induced M1 macrophage polarization and adipose tissue inflammation in vivo [25][26][27][28]. On the other hand, peroxisome proliferatoractivated receptor γ (PPARγ) and PPARδ stimulate M2 polarization of adipose tissue macrophages and thus improve systemic insulin sensitivity [29][30][31].…”
Section: Heterogeneity Of Adipose Tissue Macrophagesmentioning
confidence: 99%